Human Immune Responses to Schistosoma mansoni Vaccine Candidate Antigens - Ribeiro de Jesus, Amélia (American Society for Microbiology, 2000)
To determine the naturally occurring immunological responses to the Schistosoma mansoni antigens paramyosin, IrV-5, Sm-23 (MAP-3), and triose phosphate isomerase (MAP-4), a total of 119 subjects from an area of endemicity for schistosomiasis, including “resistant” subjects (n = 17) were evaluated. Specific immunoglobulin G1 (IgG1), IgG2, IgG3, IgG4, and IgA levels for each of the antigens and the cytokine profile in culture supernatants from antigen-stimulated peripheral blood mononuclear cells (PBMC) were determined. Although all the subjects had a high degree of contaminated water exposure, their infection levels were variable (0 to 1,128 eggs/g of stool). There were direct correlations between infection levels and levels of SWAP- and paramyosin-specific IgG1 and IgG4 (P < 0.05). However, an inverse correlation between infection levels and specific IgG2 to IrV-5 (P < 0.01) was observed. The evaluation of the cytokine profile (interleukin 5 [IL-5], IL-10, gamma interferon [IFN-γ], and tumor necrosis factor alpha) in response to these antigens showed inverse correlations between the degree of infection and IFN-γ levels in PBMC supernatants stimulated with paramyosin (P < 0.05) and IrV-5 (P < 0.01). Additionally, inverse correlations between the degree of infection and IL-5 levels in MAP-3- and MAP-4-stimulated PBMC supernatants (P < 0.01) were found. Logistic regression analysis was performed to adjust the results of cytokine profile by age. IL-5 production in MAP-3-stimulated PBMC supernatants was associated with lower infection levels (odds ratio = 11.2 [95% confidence interval, 2.7 to 45.8]).